Exploiting complementarity of carbon pricing instruments for low-carbon development in the People's Republic of China - Jie Wu; Ying Fan; Govinda R. Timilsina; Yan Xia (Asian Development Bank Institute (ADBI), 2022)
There is an urgent need to mitigate global warming for all countries around the world. The People's Republic of China (PRC) has announced a series of energy and climate policy targets in contributing its efforts towards meeting the ambitious goals in the Paris Agreement and the newly pledged carbon-neutral target. While carbon pricing has been considered the first-best policy worldwide to combat climate change, it may not be sufficient for meeting the multiple goals in the PRC, unless it is combined with complementary policies. In an attempt to explore whether this is the case, in this paper we investigate whether a single cost-effective instrument is adequate for developing a low-carbon economy in the PRC or whether a policy portfolio would be more effective. We compare the potential impacts of an emissions trading scheme (ETS), a carbon tax (CT), and a combination of an ETS and a CT. In addition, we further evaluate the economic impacts of two different policy portfolios by combining these approaches with subsidies for energy-efficient vehicles. Our results show that, while a nationwide ETS certainly has advantages over a CT regarding GDP losses, it also performs better in promoting the transfer of labor and capital from the eastern regions to central and western regions. However, a single ETS is less effective in regard to industrial structure adjustments and emission reductions in sectors that are not included in the ETS, such as the transportation sector. The results also show that a policy portfolio could achieve the same emissions reduction target with more moderate impacts. Therefore, it is suggested that implementation of a CT for sectors that are excluded from the ETS or a subsidy for energy-efficient vehicles could be considered as supplementary policies for the ETS in the PRC.
Keywords: C68; O13; Q56; 330; carbon pricing; carbon tax; emissions trading scheme; computable general equilibrium model